Light metals 2010 : proceedings of the technical sessions presented by the TMS Aluminum Committee at the TMS 2010 Annual Meeting & Exhibition, Seattle, Washington, USA, February 14-18, 2010 - Johnson, John A. (Minerals, Metals and Materials Society, 2010)
Annotation